Pathways of physical activity behavior after an intervention with students from vulnerable areas: a cluster randomized controlled trial based on a socioecological approach - Jaqueline Aragoni da Silva; Valter Cordeiro Barbosa Filho; Alexsandra da Silva Bandeira; Kelly Samara da Silva; Jorge Mota (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Efforts are needed to better understand what are the effective pathways that can optimize success in school-based physical activity interventions. This study aimed to investigate the mediators of a school-based intervention in the practice of physical activity in Brazilian students. The Fortaleça sua Saúde [Strengthen Your Health] program followed 1,085 students (11-18 years) over a semester. This multi-component intervention included training teachers, offering physical activity opportunities, and health education. Self-reported moderate-to-vigorous physical activity and potential mediators (attitude, self-efficacy, social support, perceived neighborhood environment, and physical activity facilities at school) were assessed. The product of coefficient analysis was performed. The sample was composed of 1,085 students (51.5% boys). The total effect of the intervention was 0.706 (95%CI: 0.276; 1.136). A total of 40% of the intervention effect on moderate-to-vigorous physical activity was explained by attitude towards physical activity and social support from friends and teachers. Social support from friends was a significant mediator only among boys (ab: 0.113, 95%CI: 0.027; 0.256), and social support from teachers only among girls (ab: 0.135, 95%CI: 0.019; 0.328); indicating a statistically significant indirect effect of the program on moderate-to-vigorous physical activity via these mediators. A relevant part of the effect of a multicomponent intervention on physical activity among students from vulnerable areas is explained by changes via variables at different levels of the socioecological model, including social support from friends and teachers, and attitude towards physical activity. These results should be considered in public policies.